2017
DOI: 10.1007/s40265-017-0804-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment and Management of Delirium in the Palliative Care Setting

Abstract: Delirium is a neurocognitive syndrome arising from acute global brain dysfunction, and is prevalent in up to 42% of patients admitted to palliative care inpatient units. The symptoms of delirium and its associated communicative impediment invariably generate high levels of patient and family distress. Furthermore, delirium is associated with significant patient morbidity and increased mortality in many patient populations, especially palliative care where refractory delirium is common in the dying phase. As th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 153 publications
1
96
0
9
Order By: Relevance
“…In addition, the Kaiser-Meyer-Olkin statistical measure of sampling adequacy was 0.93, which exceeded the recommended value of 0.6. Moreover, Bartlett's test of sphericity achieved statistical significance (χ 2 [45] = 1957.2; p < .001), which supported the factorability of the correlation matrix. Furthermore, all of the diagonals of the anti-image correlation matrix exceeded 0.9, which supported the inclusion of each item in the factor analysis.…”
Section: Resultsmentioning
confidence: 81%
“…In addition, the Kaiser-Meyer-Olkin statistical measure of sampling adequacy was 0.93, which exceeded the recommended value of 0.6. Moreover, Bartlett's test of sphericity achieved statistical significance (χ 2 [45] = 1957.2; p < .001), which supported the factorability of the correlation matrix. Furthermore, all of the diagonals of the anti-image correlation matrix exceeded 0.9, which supported the inclusion of each item in the factor analysis.…”
Section: Resultsmentioning
confidence: 81%
“…21 The detection of delirium is vital because its presence indicates acute systemic or central nervous system illness, physiological disturbance and drug intoxication or withdrawal; indeed, failure to detect delirium in the acute setting is associated with worse outcomes. 22 The specific management of delirium is of obvious and immediate benefit to patients in many clinical situations, for example in reversing opioid toxicity, enabling the treatment of peripheral infections that have presented with delirium, alleviating distress caused by anxiety and disorientation as well as directly by frightening delusions and hallucinations, 13,[23][24][25] and prompting more thorough assessment and treatment of symptoms. 26 For example, some studies 27 have found that surgical patients with delirium receive less analgesia than those with normal cognition; this matters not only because pain treatment is an end in itself but also because pain is itself a cause of delirium.…”
Section: Delirium: Backgroundmentioning
confidence: 99%
“…Of course, you may additionally add drugs that increase sedation, but in the case of psychotic disorders, essential treatment always takes place using neuroleptics. 13 There is basically no rule about the most recommended means, this is done in relation to the current clinical situation of the patient. Rather, a strong neuroleptic should be used (eg, a Rossperidone 0.5-5 mg/d, olanzapine 5-20mg/ d), therefore the administered doses will be lower than in the case of weak neuroleptics (quetiapine 50-250mg/d).…”
Section: Psychotic Disorders and Deliriummentioning
confidence: 99%